Study on Cannabis Compounds: An approach to Pharmacotherapy for Epilepsy in Children - Mariana Babayeva; Paramita Basu; Zvi G. Loewy (Technological Innovation in Pharmaceutical Research Vol. 10, 2021)
Epilepsy in children is a complex disease, with a variety of distinct syndromes and many alternative treatment options. Even with a plethora of available treatment options, childhood epilepsies are commonly associated with seizures that are resistant to existing treatment methods. Treatment of pediatric epilepsy is challenging and requires more effective therapy to avoid short-term and long-term neurological disorders. Marijuana has been used to treat disease since ancient times. Marijuana ingredients Cannabidiol (CBD) and D9-Tetrahydrocannabinol (THC) have created a significant research interest as potential therapy options in epilepsy treatment. THC is the major psychoactive component of marijuana that aids in reducing epileptic seizures. CBD has proven to have anticonvulsant effect not only in experimental models but also in clinical studies. Research studies have provided strong evidence for safety and anticonvulsant properties of medical marijuana. Principal concerns regarding the use of medical marijuana in children include lack of standardization and regulation, imprecise dosing, possible adverse side effects and medication interactions.